Sosialisasi Pembentukan Karakter Melalui Nilai-nilai Akhlak Yang Mulia Pada Kegiatan Pesantren Kilat Di Gampong Lengkong Kecamatan Langsa Baro - Khairunnisa; Muhammad Agus Salim; Nurul Kholis; Khairil Umam (peduli riset dan pengabdian masyarakat, 2025)
This study aims to analyze the socialization of character formation through noble moral values ​​in the activities of the short-term Islamic boarding school in Gampong Lengkong, Langsa Baro District. The short-term Islamic boarding school activity is one of the efforts to instill religious and moral values ​​in the younger generation, so that it is expected to form a good character and noble morals. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the socialization of noble moral values ​​in the short-term Islamic boarding school activities includes teaching about honesty, discipline, responsibility, and mutual respect. In addition, this activity also involves active participation from the community and parents, who play an important role in supporting the process of forming children's character. Thus, the short-term Islamic boarding school in Gampong Lengkong not only functions as a place to learn religion, but also as a means to form a generation with good morals and ready to face the challenges of the times. This study is expected to contribute to the development of character education in the Islamic boarding school environment and the wider community.